Senile Dementia from Neuroscientific and Islamic Perspectives - Tumiran, Mohd Amzari (Journal of religion and health, 2018)
Diseases involving the nervous system drastically change lives of victims and commonly increase dependency on others. This paper focuses on senile dementia from both the neuroscientific and Islamic perspectives, with special emphasis on the integration of ideas between the two different disciplines. This would enable effective implementation of strategies to address issues involving this disease across different cultures, especially among the world-wide Muslim communities. In addition, certain incongruence ideas on similar issues can be understood better. The former perspective is molded according to conventional modern science, while the latter on the analysis of various texts including the holy Qur'an, sunnah [sayings and actions of the Islamic prophet, Muhammad (pbuh)] and writings of Islamic scholars. Emphasis is particularly given on causes, symptoms, treatments and prevention of dementia.